2022
DOI: 10.1002/hed.27037
|View full text |Cite
|
Sign up to set email alerts
|

Post‐acute health care needs of people with head and neck cancer: Mapping health care services, experiences, and the impact of rurality

Abstract: Background: People with head and neck cancer (HNC) have complex health care needs; however, limited evidence exists regarding the nature or patterns of service access and use. This study explored the post-discharge health care needs and experiences of individuals with HNC from metropolitan and rural areas. Methods: Health care appointments and services accessed by people with HNC were collated for 6-month post-treatment. Data analysis of the whole cohort examined patterns of access while journey mapping integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Care fragmentation is a known risk factor for poorer overall outcomes and death in surgically treated HNC cases from the United States 17,44 and a scenario that disproportionately affects non‐metropolitan populations 44 . Although poorer survival was not found in this study, prior work in QLD, Australia, has indicated that care fragmentation can significantly impact the quality of care delivery and the experience of recovery in rural people with HNC 45 . Further examination of how care fragmentation impacts on recovery and ways to minimise these impacts is warranted given the high degree of readmission to alternative health facilities identified in the current study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Care fragmentation is a known risk factor for poorer overall outcomes and death in surgically treated HNC cases from the United States 17,44 and a scenario that disproportionately affects non‐metropolitan populations 44 . Although poorer survival was not found in this study, prior work in QLD, Australia, has indicated that care fragmentation can significantly impact the quality of care delivery and the experience of recovery in rural people with HNC 45 . Further examination of how care fragmentation impacts on recovery and ways to minimise these impacts is warranted given the high degree of readmission to alternative health facilities identified in the current study.…”
Section: Discussionmentioning
confidence: 55%
“…44 Although poorer survival was not found in this study, prior work in QLD, Australia, has indicated that care fragmentation can significantly impact the quality of care delivery and the experience of recovery in rural people with HNC. 45 Further examination of how care fragmentation impacts on recovery and ways to minimise these impacts is warranted given the high degree of readmission to alternative health facilities identified in the current study. Accessing health services closer to home is desirable for people from rural areas, it is important for health services to ensure there is access to quality care and that clinical information pertinent to their cancer recovery is accessible across facilities.…”
Section: Discussionmentioning
confidence: 97%
“…In the current study, we classified settings included in “ The Optimal Care Pathway for People with Head and Neck Cancers ,” 37 and this showed an overwhelming trend for hospital focused research. HNC multidisciplinary care is predominantly provided in larger metropolitan centers rather than throughout the community, 41 so it is perhaps not surprising that most research is conducted within these centers. In addition, another possible reason is that “health care” is still conceptualized as hospital‐based care, including inpatient and outpatient care, rather than the broader definition used (including areas such as community‐based support services, services for specific cultural groups or accommodation and financial support services) and these components may not be widely considered “health care.” The findings of this scoping review may reflect a paucity of research in these areas, or the yield may have been limited by including the concept of health care in the search terms.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a large breadth of studies totaling 95 papers was found across many aspects of health care. For people with cancer, including those with HNC, delivery of care throughout the continuum often involves multiple health care providers and touchpoints, 40,41 and this is highlighted by the heterogeneity of the data in this study. However, there remains health care components that are not represented in the yield.…”
Section: Discussionmentioning
confidence: 99%
“…These treatment plans often include a combination of surgery, radiation, chemotherapy, and immunotherapy (9,11). As a result of their complex treatment plans, and vulnerability to physical and psychological effects from HNC and its associated treatments, patients with HNC are some of the highest users of healthcare resources (12)(13)(14). As this patient population requires care from many healthcare providers across different healthcare settings, they consequently experience many transitions in care (TiC) (9,15,16).…”
mentioning
confidence: 99%